2017
DOI: 10.1177/1460408617706388
|View full text |Cite
|
Sign up to set email alerts
|

A report of two years of pre-hospital blood transfusions by Thames Valley Air Ambulance

Abstract: Introduction: Thames Valley Air Ambulance have carried two units of red blood cells on board both the aircraft and rapid response car since 2014. Methods: A retrospective database narrative review of patients receiving blood was carried out. Results: Data were analysed for 63 patients, the age range was 13 years to 89 years and 74.6% were male. Blunt trauma was the mechanism of injury in 84%. Overall, 16% of patients died at scene, 32% died either in the Emergency Department or as a hospital inpatient and 52% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…Blunt injury was most prevalent in the included studies, ranging from 55% to 100% of trauma patients . The mean or median injury severity score (ISS) varied from 18 to 43 (Table ) . The most frequent mechanisms of injury were motor vehicle collisions (42%‐88%) and falls from a height (3.4%‐13%) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Blunt injury was most prevalent in the included studies, ranging from 55% to 100% of trauma patients . The mean or median injury severity score (ISS) varied from 18 to 43 (Table ) . The most frequent mechanisms of injury were motor vehicle collisions (42%‐88%) and falls from a height (3.4%‐13%) …”
Section: Resultsmentioning
confidence: 99%
“…The mean or median injury severity score (ISS) varied from 18 to 43 (Table ) . The most frequent mechanisms of injury were motor vehicle collisions (42%‐88%) and falls from a height (3.4%‐13%) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients treated by a civilian EMS, 5 studies reported a mean/median of 1 unit transfused, 17 studies report a mean/median of 1.1 to 2 units (or between 280 and 560 mL) and 8 studies reported a mean/median of 2.3 to 3 units transfused (or between 560 and 840 mL) . Paediatric patients received a mean of 9.8 mL/kg or 255 mL (8 mL/kg) …”
Section: Resultsmentioning
confidence: 99%